2020
DOI: 10.15407/ujpe65.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Impact Excitation of the 5p55d6s2 Autoionizing States in Ba Atom

Abstract: The excitation cross-sections for the 5p55d6s2 autoionizing states of Ba atoms are studied experimentally and theoretically in an electron-impact energy range from the excitation thresholds of the states up to 600 eV. Experimental data are obtained by determining the intensities of lines in the ejected-electron spectra measured at an observation angle of 54.7∘. The incident-electron and ejected-electron energy resolutions are 0.2 eV and 0.07 eV, respectively. The calculations are performed in the distorted wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The spectroscopic assignment and the analysis of the decay channels of the 5p 5 𝑛𝑙𝑛 ′ 𝑙 ′ 𝑛 ′′ 𝑙 ′′ states in Ba atoms [14] have shown that reaction (4) is the most preferred channel for the decay of atomic states with excitation thresholds above 21 eV. Their resonant excitation character [15] explains the rapid increase in the ionization cross-sections at threshold energies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectroscopic assignment and the analysis of the decay channels of the 5p 5 𝑛𝑙𝑛 ′ 𝑙 ′ 𝑛 ′′ 𝑙 ′′ states in Ba atoms [14] have shown that reaction (4) is the most preferred channel for the decay of atomic states with excitation thresholds above 21 eV. Their resonant excitation character [15] explains the rapid increase in the ionization cross-sections at threshold energies.…”
Section: Resultsmentioning
confidence: 99%
“…The Auger spectra corresponding to the decay of the 5p 5 𝑛𝑙𝑛 ′ 𝑙 ′ states (see reaction (3)) were measured by employing the electron spectrometer [11] shown schematically in Fig. 1.…”
Section: Apparatus and Measuring Proceduresmentioning
confidence: 99%
“…The measurements were carried out on a electron-atom collision setup, which has been previously employed in a number of studies of the electron spectra of metal vapors [34,35]. In the present study, two different sources of incident electrons have been employed: an electrostatic 127°monochromator with the energy resolution of 0.2eV (FWHM) was used for the near-threshold energy region and a five-electrode electron gun with the energy spread of the beam 0.5eV (FWHM) was used at the energies beyond 50eV [36].…”
Section: Measurement and Calculation Techniquementioning
confidence: 99%
“…The energy spectrum of Auger electrons e A lies between 10.2 and 18.4 eV and, therefore, it partially overlaps with the spectrum of ejected electrons formed due to the decay of the 4p 5 nln ′ l ′ n ′′ l ′′ atomic autoionizing states [19][20][21][22][23]. However, the study of ejected-electron spectra in a wide range of impact energies, including in the near-threshold region, makes it possible to distinguish atomic and Auger lines due to the higher excitation thresholds of the latter.…”
Section: Introductionmentioning
confidence: 99%